Carbon Storage of Superior Clonal Teak Stand in Special Purpose Forest Area of Wanagama, Special Region of Yogyakarta - Sausani Nabila Afafi; Khairudin Iqbal Supartha; Heni Fatmawati; Nur Hayma Eka Sari; Jovian Dito Rissaldy; Farahdhila Yasmin Al-Husna; Fikri Danang Himawan; Muthia Aulia; Muhamad Bintang Ardiansyah; Budi Mulyana (Jurnal GALAM, 2022)
A special-purpose forest area (KHDTK) is the forest area which the purposes are for teaching and research activities. One of the research conducted in KHDTK Wanagama was examining the planting of superior Teak from breeding (jati Mega). The growth of clonal teak data can also be assessed for its carbon stock. Hence, the purpose of this research was to determine the potential of biomass and carbon stock in the Jati Mega stands at KHDTK Wanagama, Yogyakarta. The research was carried out using a non-destructive method which used the allometric equation Bt = 0.0149(D2.H)1.0855. Carbon value was calculated as 50% of the total biomass. The results showed that after 17 years of planting Jati Mega, the stand density was 665 trees/ha, carbon storage was 59.98 Mg C/ha, and carbon uptake was 220.11 Mg/ha (CO2-eq). The total value of biomass, carbon stock, and carbon dioxide removal by Jati Mega stands at KHDTK Wanagama was in the medium category. The advantage of this research is for understanding the environmental services of jati Mega as a forest carbon stock. Information on forest carbon stock can be used as basic data for forest management as climate change mitigation.Keywords: superior teak, climate change mitigation, carbon accounting, environmental services